Assessing quality of life among older persons using WHOQOL-BREF tool – a pilot study in Chandragiri, Municipality - Joshi, Kapil Dev; Thapa, Jeevan; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: The population of older persons is increasing globally, and Nepal is also showing a similar trend. WHOQOL-BREF is a widely used tool for assessing the Quality of Life (QoL), whose Nepali version is also available but is not validated in the local context. Thus, a pilot study was conducted among older people using WHOQOL-BREF to assess its internal consistency and establish its reliability and validity in the local context.Method: It was a cross-sectional quantitative study done among 30 older persons of Chandragiri Municipality-04, Kathmandu. The interviews were done in the Nepali language using a semi-structured questionnaire with a WHOQOL-BREF Nepali version after finalizing it through pretesting done among 7 older persons in Patan Hospital, Lalitpur.Result: Pre-testing revealed comprehension issues with WHO-BREF questionnaire items (1, 4, 11, 21). Modifications were made based on participant feedback. The overall alpha reliability in this pilot study was 0.75, compared to 0.84 in the field study by WHO. The alpha reliability for the domains was also comparable and slightly lower than the WHO field study. The cut-off scores based on Q1 and Q2 were determined as 80 and 66 respectively.Conclusion: The Nepali version of WHOQOL–BREF displayed sufficient alpha reliability, signaling it as a dependable instrument to use in the local context. Thus, the main study planned among older persons in Bheemdatta municipality seems to be feasible using the WHOQOL-BREF Nepali version.